2015
DOI: 10.1177/0306624x15619165
|View full text |Cite
|
Sign up to set email alerts
|

Arsonists and Violent Offenders Compared: Two Peas in a Pod?

Abstract: Arsonists are considered a type of violent offender by some and a distinct group of offenders by others. Assuming the latter could be beneficial to offer tailor-made psychotherapeutic treatment to these offenders. The present study investigated whether arsonists ( n = 55) and violent offenders ( n = 41) are differentiable regarding several demographic and personal characteristics, and criminal career. Results indicated that arsonists were significantly more often diagnosed with a Diagnostic and Statistical Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…They found that 45% of known firesetters received a further arson conviction, compared with 32% of other offenders. In contrast, Wilpert et al (2017) found that a smaller proportion of arsonists received a conviction for any offense, during an average of 9.3 years, relative to domestic violence offenders (47% vs. 61%, respectively). However, Wilpert et al also found that 9% of arsonists received a further conviction for arson, compared with 2% of violent offenders.…”
mentioning
confidence: 78%
“…They found that 45% of known firesetters received a further arson conviction, compared with 32% of other offenders. In contrast, Wilpert et al (2017) found that a smaller proportion of arsonists received a conviction for any offense, during an average of 9.3 years, relative to domestic violence offenders (47% vs. 61%, respectively). However, Wilpert et al also found that 9% of arsonists received a further conviction for arson, compared with 2% of violent offenders.…”
mentioning
confidence: 78%
“…Within a sample of offenders, firesetting was associated with early onset and severity of antisocial behavior (Stickle & Blechman, 2002). Extreme antisocial behavior has also been associated with adolescent firesetting (Martin et al, 2004), as has being more socially isolated with poorer coping skills than young offenders more generally (Wilpert, van Horn, & Eisenberg, 2017). Becker, Stuewig, Herrera, and McCloskey (2004) found firesetting predicted both violent and nonviolent later delinquency, and child firesetters were 3 times more likely to be referred to juvenile court in adolescence, even after controlling for conduct disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, among a sample of adults in the United States, Vaughn and colleagues (2010) found that, after adjusting for sociodemographic variables, psychiatric disorders, and a family history of antisocial behavior, lifetime alcohol use disorder, marijuana use disorder, CD, obsessive-compulsive disorder, and antisocial personality disorder were predictive of fire setting. In another sample of adult fire setters, Wilpert et al (2017) found that, compared to violent offenders, more fire setters had a personality disorder, high levels of social isolation, and poor coping skills.…”
Section: Psychopathologymentioning
confidence: 96%